Reducing return of disease activity in patients with relapsing multiple sclerosis transitioned from natalizumab to teriflunomide: 12-month interim results of teriflunomide therapy. Issue 1 (January 2019) - Cohan, Stanley L; Edwards, Keith; Lucas, Lindsay; Gervasi-Follmar, Tiffany; O'Connor, Judy; Siuta, Jessica; Kamath, Vineetha; Garten, Lore; Chen, Chiayi; Thomas, James; Smoot, Kyle; Kresa-Reahl, Kiren; et al.
Background: Natalizumab is an effective treatment for relapsing multiple sclerosis. Return of disease activity upon natalizumab discontinuance creates the need for follow-up therapeutic strategies. Objective: To assess the efficacy of teriflunomide following natalizumab discontinuance in relapsing multiple sclerosis patients. Methods: Clinically stable relapsing multiple sclerosis patients completing 12 or more consecutive months of natalizumab, testing positive for anti-John Cunningham virus antibody, started teriflunomide 14 mg/day, 28 ± 7 days after their final natalizumab infusion. Physical examination, Expanded Disability Status Scale, laboratory assessments, and brain magnetic resonance imaging were performed at screening and multiple follow-up visits. Results: Fifty-five patients were enrolled in the study. The proportion of patients relapse-free was 0.94, restricted mean time to first gadolinium-enhancing lesion was 10.9 months and time to 3-month sustained disability worsening was 11.8 months. The mean number of new or enlarging T2 lesions per patient at 12 months was 0.42. Exploratory analyses revealed an annualized relapse rate of 0.08, and a proportion of patients with no evidence of disease activity of 0.68. Forty-seven patients (85.5%) reported adverse events, 95% of which were mild to moderate. Conclusions: Teriflunomide therapy initiated without natalizumab washout resulted in a low rate of return of disease activity. Clinicians may consider this a worthwhile strategy when transitioning clinically stable patients off natalizumab to another therapy. ClinicalTrials.gov Identifier: NCT01970410